How Students Prepare and Perform: A Project-Based Study on English Conversations and Individual Presentations - Puspa Fortuna Zulfa; Ika Purnama Sari (Journal of Educational Sciences, 2026)
This study examines how university students prepare and perform English conversations and individual presentations within a Project-Based Learning (PjBL) framework. The purpose of the study was to examine the relationship between students’ preparation processes and their speaking performance, documented through video submissions. A qualitative descriptive design with supporting quantitative data was used. Approximately 200 university students participated in a project-based speaking task, and a representative sample of the recorded videos was analyzed using a performance rubric focusing on fluency, accuracy, organization of ideas, interaction, nonverbal delivery, and evidence of preparation. Findings indicated that most students demonstrated strong preparation strategies, including scripting, rehearsal, peer collaboration, and self-reflection. Video analysis revealed that the majority achieved “Excellent” and “Good” levels of performance across key criteria, particularly in organization and interaction, while only a small minority needed improvement. Discussion highlighted that structured preparation significantly contributed to students' confidence, coherence, and communicative effectiveness. The study concluded that PjBL facilitates not only linguistic development but also learner autonomy and engagement. These results suggest that integrating documented video projects in EFL classes can effectively improve both the preparation process and observable speaking performance outcomes.